Isolation and characterization of an exopolysaccharide‐producing Leuconostoc citreum strain from artisanal cheese. (18th October 2018) - Domingos‐Lopes, M.F.P.; Lamosa, P.; Stanton, C.; Ross, R.P.; Silva, C.C.G.
Abstract: High molar mass exopolysaccharides (EPS) produced from sucrose by lactic acid bacteria (LAB) are of great interest as natural additives to use in foods, medical and pharmaceutical industry. This study aimed to identify the EPS produced by Leuconostoc citreum L3C1E7 isolated from Pico cheese and characterize the strain for technological and probiotic potential. Purified EPS was isolated from the culture of L. citreum L3C1E7 by ethanol precipitation, with a yield of 520 mg ml −1 . The EPS‐producing strain had a mucoid phenotype and average molecular weight of 5·88 × 10 6  Da. The structural characterization of the purified EPS was determined by 1 H, 13 C and two‐dimensional NMR spectroscopy. EPS was composed of alternating α ‐(1→6)‐linked and α ‐(1→3)‐linked D‐glucopyranyl units, suggesting the existence of an alternan. The strain was slow acidifying, produced diacetyl and displayed high esterase/lipase and aminopeptidase activities, which promote the desirable flavours in dairy products. Moreover, L. citreum showed moderate resistance to the adverse conditions of the gastrointestinal (GI) tract and high adhesion to GI cells. This work provides a better understanding of EPS produced by L. citreum and the potential application of EPS‐producing strain in food and/or as a probiotic culture. Significance and Impact of the Study: Some LAB strains are known to use extracellular glycoside‐hydrolase enzymes for synthesizing a diversity of exopolysaccharides (EPS) with potential application as natural additives to foods. Previous studies have identified an EPS‐producing Leuconostoc citreum strain with immunomodulatory properties. This work provides a better understanding of EPS produced by this strain and the potential application of the strain in food fermentation and/or as a probiotic culture. Abstract : Significance and Impact of the Study: Some LAB strains are known to use extracellular glycoside‐hydrolase enzymes for synthesizing a diversity of exopolysaccharides (EPS) with potential application as natural additives to foods. Previous studies have identified an EPS‐producing Leuconostoc citreum strain with immunomodulatory properties. This work provides a better understanding of EPS produced by this strain and the potential application of the strain in food fermentation and/or as a probiotic culture.